1993
DOI: 10.1002/ijc.2910540604
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical administration of indium‐111‐labelled hmfg2 monoclonal antibody in superficial bladder carcinomas

Abstract: Tumour-associated HMFG2 monoclonal antibody (MAb) was labelled with indium-111 and administered intravesically to 20 patients with known or suspected superficial bladder carcinoma. The antibody solution was kept in the bladder for 1 hr and was then washed out. Cystoscopy was performed at 2 and 24 hr after instillation. Radioactivity of tumour and normal tissue obtained from the bladder during cystoscopy and cells recovered from urine after the instillation were counted in a gamma-counter. Conventional histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…It is known that tumor cells have cell surface antigens that are different from those of normal cells. If the mAB bound photosensitizer will bind specifically to the tumor tissue, this would allow selective photodamage without affecting normal tissue [82]. The current strategy for binding photosensitizers uses polyphasic tumor therapy to accumulate up to 10 8 photosensitizer molecules on the tumor, assuming ca.…”
Section: Third Generation Photosensitizersmentioning
confidence: 99%
“…It is known that tumor cells have cell surface antigens that are different from those of normal cells. If the mAB bound photosensitizer will bind specifically to the tumor tissue, this would allow selective photodamage without affecting normal tissue [82]. The current strategy for binding photosensitizers uses polyphasic tumor therapy to accumulate up to 10 8 photosensitizer molecules on the tumor, assuming ca.…”
Section: Third Generation Photosensitizersmentioning
confidence: 99%
“…When the size of the tumor was taken into consideration, studies by Bamias et al [4]reported no correlation between uptake and size of the tumor. In our series, a considerable accumulation of radioactivity was observed in larger neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the ligand should be tailored to the characteristics of the tumor type studied. For urinary bladder cancer several conjugates have been constructed based on Mab as tumor–seeking molecule [3, 4, 11, 12, 13]. However, no specific bladder cancer–derived antibody has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New radioimmunotherapeutical conjugates have been developed in the last 15 years with the prospect of treating bladder cancer through such procedures. Most of these involved antibodies radiolabelled with 111 In (8,9), 131 I (10), 67 Cu (11,12), 188 Re (13). However, the large size of monoclonal antibodies (~150 kD) is a general limitation to the efficiency of intravesical treatments due to slow diffusion and limited penetration.…”
Section: Introductionmentioning
confidence: 99%